Cross‐cultural differences in information disclosure evaluated through the EORTC questionnaires. Issue 2 (3rd November 2011) - Arraras, Juan Ignacio; Greimel, Eva; Chie, Wei‐Chu; Sezer, Orhan; Bergenmar, Mia; Costantini, Anna; Young, Teresa; Vlasic, Karin Kuljanic; Velikova, Galina; ,
Abstract Objective Informational needs among cancer patients are similar, but the degree of information disclosure in different cultural areas varies. In this paper, we present the results of a cross‐cultural study on information received. Methods The EORTC information questionnaire, EORTC QLQ‐INFO25, was administered during the treatment process. This questionnaire evaluates the information that patients report they have received. Cross‐cultural differences in information have been evaluated using statistical tests such as Kruskall–Wallis and multivariate models with covariates to account for differences in clinical and demographic characteristics across areas. Results Four hundred and fifty‐one patients from three cultural areas, North–Middle Europe, South Europe, and Taiwan, were included in the study. Significant differences among the three cultural areas appeared in eight QLQ‐INFO25 dimensions: information about the disease; medical tests; places of care; written information; information on CD/tape/video; satisfaction; wish for more information; and information helpfulness. North–Middle Europe patients received more written information (mean = 67.2 (North) and 33.8 (South)) and South Europe patients received more information on different places of care (mean = 24.7 (North) and 35.0 (South)). Patients from North–Middle Europe and South Europe received more information than patients from Taiwan about the disease (mean = 57.9, 60.6, and 47.1, respectively) and medical tests (70.9, 70.4, and 54.5), showed more satisfaction (64.8, 70.2, and 35.0), and considered the information more helpful (71.9, 73.9, and 50.4). These results were confirmed when adjusting for age, education, and disease stage. Conclusion There are cross‐cultural differences in information received. Some of these differences are based on the characteristics of each culture. Copyright © 2011 John Wiley & Sons, Ltd.